Love in education & the art of living - Smith, Becky L. Noël; Hewitt, Randall (Studies in the philosophy of education., 2020)
"This collection of narratives, essays, and poetic expressions includes the perspectives of students and educators who, in varying ways, express gratitude toward those who came before them and a deep desire to keep the faith alive. The authors share narrative accounts of someone or something in the public schools or learning experiences in general that inspired and nurtured the passionate desire to achieve goods internal to some shared practice - that is, some art at living - such that there was a transformative readjustment to the very nature of experience itself. We share with readers the stories and intellectual habits that have fueled us, inspired us, and that continue to push us to engage in the practice of cultivating educational dynamics that are meaningful and transformative for ourselves, our students, and our communities. The piece concludes with an exploration into how teachers might not only root their craft, but the habit of love in general, in a sense of freedom"--